2020
DOI: 10.3390/antiox9111161
|View full text |Cite
|
Sign up to set email alerts
|

Oleacein Attenuates the Pathogenesis of Experimental Autoimmune Encephalomyelitis through Both Antioxidant and Anti-Inflammatory Effects

Abstract: Oxidative stress and proinflammatory cytokines are factors affecting multiple sclerosis (MS) disease progression. Oleacein (OLE), an olive secoiridoid, possesses powerful antioxidant and anti-inflammatory activities, which suggests its potential application to treat neuroinflammatory disorders. Herein, we investigated the impact of OLE on the main clinic-pathological features of experimental autoimmune encephalomyelitis (EAE), an animal model for MS, including paralysis, demyelination, central nervous system (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Hence, the increase of IL-10 secretion induced by OLC was conducive to fighting inflammation. A previous study found that OLC significantly decreased expression of pro-inflammatory cytokines (IL-1β and TNF-α), while it increased the anti-inflammatory cytokine IL-10 in an experimental model of autoimmune encephalomyelitis [44].…”
Section: Discussionmentioning
confidence: 89%
“…Hence, the increase of IL-10 secretion induced by OLC was conducive to fighting inflammation. A previous study found that OLC significantly decreased expression of pro-inflammatory cytokines (IL-1β and TNF-α), while it increased the anti-inflammatory cytokine IL-10 in an experimental model of autoimmune encephalomyelitis [44].…”
Section: Discussionmentioning
confidence: 89%
“…Oleocanthal is a phenolic compound with anticancer [ 7 , 8 ] and anti-inflammatory activity similar to ibuprofen [ 9 ] able to inhibit the progress of Alzheimer’s disease [ 10 , 11 ] as well as oleuropein aglycon [ 12 ]. Oleacein presents anti-inflammatory [ 13 ] antiatherosclerotic [ 14 ] antioxidant [ 15 ] and neuroprotective activity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have widely used the anti-in ammatory or antioxidant agents as promising medications in different neurodegenerative diseases management [16][17][18]. Moreover, natural products with antioxidant and anti-in ammatory properties have been considered as the potential therapeutic target in MS treatment [19,20,13,21,22]. Piperine is the main bioactive alkaloid ingredient of black pepper which has a wide range of pharmacological potencies including: antioxidant [23], anti-in ammatory [24,25], anti-apoptotic [17], antidepressant [26] and anticonvulsant [27] effect.…”
Section: Introductionmentioning
confidence: 99%